Investigating students ’perceptions on the effectiveness of entrepreneurship education module in developing students’ entrepreneurial competencies - Qadir, Sirwan Ahmad; Hamad, Bakhtiar Kakil (ZANCO Journal of Human Sciences., 2023)
تعد ريادة الأعمال مادة مهمة يجب تضمينها في المنهج الدراسي الجامعي إما كوحدة دراسية مستقلة أو كجزء من مواد أخرى قامت كلية التربية الأساسية بالمبادرة بإضافة هذه المادة كجزء من منهجها الدراسي في العام الدراسي 2016-2017 كان الهدف من إضافتها هو تطوير كفاءة الريادية لدى الطلاب وتخريج طلاب يلبون طلبات السوق. تهدف هذه الدراسة إلى التحقق أولا من النجاح الذي حققه الوحدة الدراسية في تنمية المواقف الريادية لدى الطلبة، وثانيا في تنمية مهاراتهم الريادية. وكذلك في تنمية معرفتهم ووعيهم الريادي تبنت هذه الدراسة منهجية وصفية حيث تم جمع بيانات كمية خلال بناء استبيان مغلق متكون من (٥٢) فقرة. بلغ عدد مشاركي الدراسة 224 طالبا في المرحلة الثانية بكلية التربية الأساسية. تم إدخال البيانات إلى برنامج (SPSS)، ثم تم تحليلها باستخدام اختبار غير المعملي لأن البيانات لم تكن موزعة بشكل طبيعي ووفقا لنتائج الدراسة، فإن الوحدة ساعدت بنجاح الطلاب في تنمية مواقفهم ومهاراتهم ومعرفتهم الريادية. وعلاوة على ذلك، أشار الطلاب إلى أنهم أصبحوا أكثر مهارة ومعرفة بعد أخذ الوحدة وتوصل الباحثان إلى مجموعة من التوصيات والمقترحات Entrepreneurship is an important module to be incorporated into the higher education curriculum either as an independent module or integrally through other subjects. College of Basic Education, as an academic institution, took the initiative of adding EE indecently to its curriculum in 2016-2017. The purpose of adding it were to develop the students ’entrepreneurial competencies and graduate students that meet market demand. The present study aims to investigate; first, how successful entrepreneurship education module is in developing students’ entrepreneurial attitudes, second, entrepreneurship education module is in developing students’ entrepreneurial skills, and third, entrepreneurship education module is in developing students’ entrepreneurial knowledge and awareness. This current study adopted a descriptive methodology in which the data was collected quantitively through the construction of a closed ended questionnaire consisting of (52) items. The participants of the study were (224) second year students at College of Basic Education. The data was entered SPSS program, then analyzed using non-parametric test because the data was not normally distributed. According to the findings of the study, the module successfully helped the students to develop their entrepreneurial attitudes, skills, and knowledge. Moreover, the students indicated that after taking the module, they became more skilled and knowledgeable about entrepreneurship and the researchers suggested a set of recommendations.